2022
DOI: 10.1126/sciimmunol.abq4531
|View full text |Cite
|
Sign up to set email alerts
|

GTF3A mutations predispose to herpes simplex encephalitis by disrupting biogenesis of the host-derived RIG-I ligand RNA5SP141

Abstract: Herpes simplex virus 1 (HSV-1) infects several billion people worldwide and can cause life-threatening herpes simplex encephalitis (HSE) in some patients. Monogenic defects in components of the type I interferon system have been identified in patients with HSE, emphasizing the role of inborn errors of immunity underlying HSE pathogenesis. Here, we identify compound heterozygous loss-of-function mutations in the gene GTF3A encoding for transcription factor IIIA (TFIIIA), a component of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“… 70 A recent study described a child afflicted by HSE who was found to harbour a compound heterozygous variant in the GTF3A gene, which encodes for the transcription factor IIIA (TFIIIA); a moonlighting protein with protective properties against HSV through production of the RIG-I ligand, RNA5SP141. 71 This patient (and his sister) exhibited a diminished IFN-I response to HSV-1 in isolated patient fibroblasts and GTF3A gene-edited cells.…”
Section: Acute Herpes Simplex Virus Encephalitismentioning
confidence: 88%
“… 70 A recent study described a child afflicted by HSE who was found to harbour a compound heterozygous variant in the GTF3A gene, which encodes for the transcription factor IIIA (TFIIIA); a moonlighting protein with protective properties against HSV through production of the RIG-I ligand, RNA5SP141. 71 This patient (and his sister) exhibited a diminished IFN-I response to HSV-1 in isolated patient fibroblasts and GTF3A gene-edited cells.…”
Section: Acute Herpes Simplex Virus Encephalitismentioning
confidence: 88%
“…Recently, Naesens and colleagues reported a case of HSE in a patient who was compound heterozygous for variants in GTF3A [ 75 ]. This gene encodes the transcription factor IIIA (TFIIIA), which is essential for POL III-mediated transcription of 5S rRNA species.…”
Section: Inborn Errors Of Interferon-dependent Innate Immunitymentioning
confidence: 99%
“…In a mechanism analogous to the guard theory of plant immunity [ 94 ], RNA 5S ribosomal 141 is released from its sequestration and can now induce the RIG-I-mediated activation of IFN-I [ 33 ] ( Figure 2 A,B). Interestingly, both the reported patient and his sister (who also harbored both GTF3A variants but did not experience HSE) had decreased IFN-I responses to HSV-1, and this could be rescued by reconstitution with WT GTF3A [ 75 ]. Both siblings also had a CVID-like phenotype [ 75 ], and, although rare, HSE is not unheard of among CVID patients, as discussed below [ 95 ].…”
Section: Inborn Errors Of Interferon-dependent Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations